Development of an Automated Counselling System for Nigerian Open and Distance Learning Students’ Programme Selection - Ukaigwe, Jane Ada; Salihu, Abdullateef Ebenmosi; Ezeanya, Christiana Uche; Okunade, Oluwasogo Adekunle; Irabor, Alexander Oseihiemen (ABUAD Journal of Engineering Research and Development (AJERD), 2025)
Choosing an academic programme or career path is often challenging for prospective students seeking admission to higher education institutions. Many rely on advice from both qualified and unqualified sources, leading to poor programme choices that result in dissatisfaction, poor performance, or dropping out. This study aims to design an Automated Counselling System (ACS) to improve prospective students’ programme and career decisions in an Open and Distance Learning (ODL) institution, using the National Open University of Nigeria (NOUN) as a case study. The ACS was developed using Client Architecture and a mixed-method approach. Data was collected through questionnaires distributed via NOUN desk officers at purposefully selected study centers across Nigeria’s six geopolitical zones. Of the 240 questionnaires distributed, 180 were returned. Findings indicate that the system was well received, with most users expressing satisfaction in its ability to assist them in making informed, long-term programme choices. The ACS presents an effective solution to the counselling gaps in educational institutions, offering a scalable and reliable alternative to traditional counselling methods. However, further research on how the system can help students manage academic challenges once they are admitted should be investigated. The insights from this study can be applied to other higher education institutions.